A prática de exercícios físicos como estratégia de promoção da saúde em pessoas com doenças crônicas não transmissíveis no programa academia da saúde de Sobral. - Albuquerque, Darlanderson Gomes (2024)
The Health Academy Program (Programa Academia da Saúde - PAS) aims to complement comprehensive care, strengthen health promotion and disease prevention, and promote healthy lifestyle practices, integrated with programs such as the Family Health Strategy, multiprofes- sional teams, and Health Surveillance. PAS promotes health through physical activity and health education practices for the population, aiming to improve Quality of Life (QoL). Non- Communicable Diseases (NCDs) are the leading cause of mortality worldwide and represent a significant public health concern globally. Among these, we can highlight Systemic Arterial Hypertension (SAH) and diabetes mellitus (DM). SAH encompasses all conditions of essential hypertension, being the primary risk factor for cardiovascular diseases. DM, on the other hand, is a metabolic disorder characterized by persistent hyperglycemia, resulting from a deficiency in insulin production, its action, or both, which can lead to irreversible damage to certain human organs. In this context, it is necessary to adopt educational measures, treatment, risk factor con- trol, health-promoting behaviors, and NCD management, which pose a challenge to public health. Therefore, health promotion and physical activity actions have been an inherent practice at all levels of care, guided by physical education professionals, with the aim of promoting health to users and providing better quality of life. This study aims to analyze the association between physical activity and the prevention or treatment of DM or SAH in PAS users in So- bral. In a sample of 60 (sixty) participants from the health academies in the municipality of Sobral, it was identified that 97% are women, primarily aged over 60 years. Of the respondents, 60% have Hypertension, 5% have Diabetes, and 35% have both SAH and DM. Quality of life was analyzed using the World Health Organization Quality of Life Brief (WHOQOL-Bref), an instrument from the World Health Organization (WHO), in two groups of users engaged in physical and complementary practices. On average, no significant differences were observed in the QoL indicators between the groups through univariate analysis, indicating that it may be related to the perception and regularity of users, regardless of the type of physical activity.